Reframing Teacher Engagement: A Framework for Improving Workplace Conditions to Foster Teacher Engagement - Heim, Katrin; Marshall, Kurtis (Alberta Journal of Educational Research, 2022)
Historically, the factors contributing to teacher engagement have been premised on the idea that engagement is grounded in intrinsic motivation and intrapersonal characteristics. This narrative literature review offers an alternative perspective, whereby teacher engagement is enhanced through creating policies to improve workplace conditions and foster engagement. Within the findings, three essential conditions to foster teacher engagement were identified: a supportive organization, active leadership, and healthy interpersonal relationships. A conceptual framework based on these findings is constructed and proposed as an aid to school leaders in policy development to improve teacher engagement. Keywords: Teacher engagement, conditions, policy, framework, school leaders Historiquement, les facteurs contribuant à l'engagement des enseignants ont été basés sur l'idée que l'engagement est fondé sur la motivation intrinsèque et les caractéristiques intrapersonnelles. Cette analyse documentaire narrative propose une autre perspective, selon laquelle l'engagement des enseignants est renforcé par la création de politiques visant à améliorer les conditions de travail et à favoriser l'engagement. Dans les conclusions, trois conditions essentielles pour favoriser l'engagement des enseignants ont été identifiées : une organisation de soutien, un leadership actif et des relations interpersonnelles saines. On construit un cadre conceptuel basé sur ces résultats et on le propose au leadership scolaire comme appui au développement de politiques visant à améliorer l'engagement des enseignants. Mots clés : Engagement des enseignants, conditions, politique, cadre, leadeurship scolaire